THE ROLE OF MORAL EDUCATION IN DEVELOPING THE PERSONALITY OF STUDENTS AT SMKN 3 PADANG - Yufa Ficanysha; Firman; Riska Ahmad (Literasi Nusantara, 2021)
Moral education is the existence of absolute and moral that morals are absolutely necessary to create a younger generation in their order understand very well which is good and right. The substance of moral education is to form a perfect personality for each child. Behavior what is expected to be born is; honest trial, helping people, respect, be responsible, appreciate, cherish, accept each other, empathy, sympathy and accept what it is. Moral education has a higher meaning, because it is not just teaching what is true and what which one is wrong, more than that moral education and character instill habit (habituation) about good things so that children understand (cognitive domain) about what is good and wrong, being able to feel (affective domain) good values ??and willing to do (domein psychomotor). As Aristotle said, the character is closely related to "Habits" or habits that are continuously practiced and done. In moral education emphasizes the importance of ordering personality with the three components of good character (the good component character) namely moral knowledge or knowledge of morals, morals feelings or feelings about morals and deeds or deeds moral